PENGARUH PENEMPATAN KERJA, KOMITMEN ORGANISASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PT. UNDIP MAJU - Restyaningsih, Tri; Juwariyah, Nurul (Solusi, 2024)
Employee performance is the result of work, both in quantity and quality, which is obtained by employees through the completion of assigned tasks in accordance with their respective authorities and responsibilities. Employees who have excellence and reliability have the opportunity to work effectively and efficiently in realizing organizational goals. Employee effectiveness indicates that employees are able to show high performance. Many factors can affect employee performance, such as work placement, organizational commitment and compensation. The purpose of this study was to analyze the effect of work placement, organizational commitment and compensation on employee performance.The population and sample of this research are employees of PT. Undip Mandiri Various Business Services, Jl. Prof. Soedarto, SH, Jl. Tembalang, Semarang amounted to 55 people using a census technique. The type of data used is primary and secondary. Methods of data collection using a questionnaire. While the analysis technique used multiple regression analysis.The results of the analysis show that: 1). Work placement is proven to affect employee performance. 2). Organizational commitment is proven to influence employee performance. 3). Compensation is proven to have an effect on employee performance.